Notch3 is activated by chronic hypoxia and contributes to the progression of human prostate cancer. Issue 11 (26th June 2013) - Danza, Giovanna; Di Serio, Claudia; Ambrosio, Maria Raffaella; Sturli, Niccolò; Lonetto, Giuseppe; Rosati, Fabiana; Rocca, Bruno Jim; Ventimiglia, Giuseppina; del Vecchio, Maria Teresa; Prudovsky, Igor; Marchionni, Niccolò; Tarantini, Francesca
Abstract : Prostate cancer (PC) is still the second cause of cancer‐related death among men. Although patients with metastatic presentation have an ominous outcome, the vast majority of PCs are diagnosed at an early stage. Nonetheless, even among patients with clinically localized disease the outcome may vary considerably. Other than androgen sensitivity, little is known about which other signaling pathways are deranged in aggressive, localized cancers. The elucidation of such pathways may help to develop innovative therapies aimed at specific molecular targets. We report that in a hormone‐sensitive PC cell line, LNCaP, Notch3 was activated by hypoxia and sustained cell proliferation and colony formation in soft agar. Hypoxia also modulated cellular cholesterol content and the number and size of lipid rafts, causing a coalescence of small rafts into bigger clusters; under this experimental condition, Notch3 migrated from the non‐raft into the raft compartment where it colocalized with the γ‐secretase complex. We also looked at human PC biopsies and found that expression of Notch3 positively correlated with Gleason score and with expression of carbonic anhydrase IX, a marker of hypoxia. In conclusion, hypoxia triggers the activation of Notch3, which, in turn, sustains proliferation of PC cells. Notch3 pathway represents a promising target for adjuvant therapy in patients with PC. Abstract : What's new? Hypoxia can play an important role in tumor progression, by altering the expression of a number of regulatory genes. In this study, the authors found that hypoxia can lead to the activation of Notch3 in prostate cancer (PC) tumor cells, by altering the membrane structure of these cells. Notch3 expression correlates with tumor grade in human cancers. The Notch signaling pathway may therefore be a promising target for adjuvant therapy in PC. Immunostaining for Notch3 may also provide a useful biomarker for identifying tumors with a poor prognosis.